Muscle ischemic preconditioning does not improve performance during self-paced exercise - Tocco, F.; Marongiu, E.; Ghiani, G.; Sanna, I.; Palazzolo, G.; Olla, S.; Pusceddu, M.; Sanna, P.; Corona, F.; Concu, A.; Crisafulli, A. (International Journal of Sports Medicine, 2015)
Muscle ischemic preconditioning (IP) has been found to improve exercise performance in laboratory tests. This investigation aims at verifying whether performance is improved by IP during self-paced exercise (SPE) in the field. 11 well-trained male runners performed 3 randomly assigned 5 000 m self-paced running tests on an outdoor track. One was the reference (RT) test, while the others were performed following muscle IP (IPT) and a control sham test (ST). Average speeds were measured during each test. Mean values in oxygen uptake (VO2), aerobic energy cost (AEC) during race and post-race blood lactate (BLa) were gathered. Data showed that none of the studied variables were affected by IPT or ST with respect to the RT test. Average speeds were 4.63±0.31, 4.62±0.31 and 4.60±0.25 m·s-1 for the RT, the ST and the IPT tests, respectively. Moreover, there was no difference among tests in speed reached during each lap. VO2 was 3.5±0.69, 3.74±0.85 and 3.62±1.19 l·min-1. AEC was 1.04±0.15, 1.08±0.1 and 1.09±0.15 kcal·kg-1·km-1. Finally, post-race BLa levels reached 12.85±3.54, 11.88±4.74 and 12.82±3.6 mmol·l-1. These findings indicate that performance during SPE is not ameliorated by ischemic preconditioning, thereby indicating that IP is not suitable as an ergogenic aid.